War Girls - Onyebuchi, Tochi (New York : Razorbill, 2019)
In 2172, when much of the world is unlivable, sisters Onyii and Ify dream of escaping war-torn Nigeria and finding a better future together but are, instead, torn apart.
Keywords: Sisters -- Juvenile fiction; Cyborgs -- Juvenile fiction; War stories; Survival -- Juvenile fiction; Sisters -- Fiction; Cyborgs -- Fiction; War -- Fiction; Survival -- Fiction; Science fiction; Nigeria -- Juvenile fiction; Nigeria -- Fiction; Science fiction